Financial Ratio Dynamics and Profitability in Indonesian Islamic Banking: A Panel Analysis of FDR, NPF, and CAR - Elvira Khairunnisa Ibrahim; Muhammad Albahi; Raja Sakti Putra Harahap (Politeknik Ganesha Medan, 2026)
This study addresses inconsistencies in prior empirical findings regarding the relationship between financial ratios and profitability in Islamic banking, where theoretical predictions often diverge from observed data. Despite growing scholarly interest in Islamic bank performance, limited post-pandemic evidence exists on how Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and Capital Adequacy Ratio (CAR) jointly influence Return on Assets (ROA). This study employs a quantitative approach using panel data regression with Ordinary Least Squares (OLS) estimation on four Islamic Commercial Banks registered with the Financial Services Authority (OJK), selected through purposive sampling. Results indicate that FDR, NPF, and CAR each exert a positive and significant partial effect on ROA, and simultaneously explain 76.5% of ROA variation (F = 46.628, p < 0.05). These findings challenge conventional assumptions — particularly regarding NPF — and suggest that prudent financing management in the post-pandemic recovery period may alter the expected direction of risk-profitability relationships. This study contributes by providing recent post-pandemic empirical evidence on Islamic bank financial performance in Indonesia, offering implications for both regulatory policy and bank management strategy.